2023
DOI: 10.1002/adma.202307822
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Trafficking of Nanotechnology‐Mediated mRNA Delivery

Pei Huang,
Hongzhang Deng,
Changrong Wang
et al.

Abstract: Messenger RNA (mRNA)‐based therapy has emerged as a powerful, safe, and rapidly scalable therapeutic approach that involves technologies for both mRNA itself and the delivery vehicle. Although there are some unique challenges for different applications of mRNA therapy, a common challenge for all mRNA therapeutics is the transport of mRNA into the target cell cytoplasm for sufficient protein expression. This review is focused on the behaviors at the cellular level of nanotechnology‐mediated mRNA delivery system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 308 publications
0
5
0
Order By: Relevance
“…For example, mRNA NPs with smaller sizes demonstrate enhanced tissue penetration, whereas those with larger sizes exhibit superior tissue accumulation and retention . The impact of surface charges on the in vivo tropism of mRNA NPs has been widely recognized, namely, highly positively charged mRNA NPs are more inclined to target the lungs, while negatively charged ones accumulate more in the spleens. , The surface properties, like poly­(ethylene glycol) (PEG) modification, also can influence NP pharmacokinetics and cell interactions . Notably, apart from direct impacts on in vivo organ/tissue/cell tropism, these physiochemical properties also influence surface protein adsorption and further affect endogenous targeting . , For example, NPs with negative charges (ζ < −10 mV) tend to bind to opsonins, resulting in rapid sequestration in mononuclear phagocyte system (MPS) organs.…”
Section: Passive Targetingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, mRNA NPs with smaller sizes demonstrate enhanced tissue penetration, whereas those with larger sizes exhibit superior tissue accumulation and retention . The impact of surface charges on the in vivo tropism of mRNA NPs has been widely recognized, namely, highly positively charged mRNA NPs are more inclined to target the lungs, while negatively charged ones accumulate more in the spleens. , The surface properties, like poly­(ethylene glycol) (PEG) modification, also can influence NP pharmacokinetics and cell interactions . Notably, apart from direct impacts on in vivo organ/tissue/cell tropism, these physiochemical properties also influence surface protein adsorption and further affect endogenous targeting . , For example, NPs with negative charges (ζ < −10 mV) tend to bind to opsonins, resulting in rapid sequestration in mononuclear phagocyte system (MPS) organs.…”
Section: Passive Targetingmentioning
confidence: 99%
“…Ligand-mediated active targeting can facilitate the binding of mRNA NPs with particular cell receptors and/or cellular internalization , thus achieving targeted delivery of mRNA to the cells of interest . Commonly used targeting ligands for site-specific mRNA delivery include small molecules, carbohydrates, nucleic acids, peptides, and antibodies. , These targeting ligands can be incorporated into mRNA nanocarriers through prefabrication modification strategies (suitable for tolerable entities such as small molecules and peptides) or postfabrication modification strategies (suitable for sensitive entities such as antibodies), driven by covalent coupling (e.g., esterification, amidation, thiol–maleimide Michael addition, azide–alkyne click chemistry, and Diels–Alder reaction) or noncovalent interactions (e.g., electrostatic interaction, hydrogen bonding, hydrophobic interaction, affinity avidin–biotin interaction, and host–guest interaction). , For instance, Robinson et al modified ionizable LNPs with CD3 or CD8 antibody for delivering mRNA to T cells . Another study identified a tumor-specific peptide through phage display, which facilitated active targeting of mRNA LNPs for hepatocellular carcinoma (HCC) therapy. , …”
Section: Active Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] To achieve effective mRNA therapies, it is imperative that the mRNAs reach the cytoplasm and be translated into therapeutic proteins. [7][8][9] However, the transfection effect of naked mRNA is limited due to defects such as rapid degradation by nucleases, restricted cellular uptake, and inherent immunogenicity. 10 Consequently, the creation of stable, efficacious, and safe delivery systems is crucial for mRNA application.…”
Section: Introductionmentioning
confidence: 99%
“…11 Common challenges for mRNA delivery platforms include improving translation efficiency, promoting high mRNA stability, possessing favourable pharmacokinetic profiles, achieving organ or cell selectivity and employing simple manufacturing and storage. 9 These all emphasize that a qualified mRNA delivery platform requires careful design. paved the way for extensive development of mRNA therapeutics.…”
Section: Introductionmentioning
confidence: 99%